1, 1-Disubstituted olefin synthesis via Ni-catalyzed Markovnikov hydroalkylation of alkynes with alkyl halides. Issue 30 (22nd March 2016) - Lu, Xiao-Yu; Liu, Jing-Hui; Lu, Xi; Zhang, Zheng-Qi; Gong, Tian-Jun; Xiao, Bin; Fu, Yao
Abstract : A Ni-catalyzed Markovnikov hydroalkylation of alkynes with alkyl halides is described. Abstract : A Ni-catalyzed Markovnikov hydroalkylation of alkynes with alkyl halides is described. The reaction proceeds smoothly without the use of sensitive organometallic reagents and shows good functional-group compatibility, enabling the efficient synthesis of a variety of 1, 1-disubstituted olefins. It also provides a straightforward approach for the modification of complex organic molecules.